On Gender and Apology: Case of Algerian Arabic - N. Derki (Дискурс профессиональной коммуникации, 2023)
The present study explores the impact of gender on the use of apology strategies by Algerian speakers. Speciﬁcally, the research aims to identify the apology strategies utilized by male and female Algerian participants and to examine the potential inﬂuence of gender on such usage. The study employed a discourse completion task (DCT) as its methodological tool for data collection. The DCT included nine scenarios in which participants were required to provide an apology. Sixty participants, consisting of 30 males and 30 females, were recruited for the study. Both qualitative and quantitative analyses were employed to examine the data collected. To facilitate the analysis, a modiﬁed version of Blum-Kulka and Olshtain’s (1984) framework was applied, given its widespread usage and convenience in similar studies. The ﬁndings of the study indicate that male and female Algerian participants employed seven primary apology strategies, and gender inﬂuenced the frequency of their usage. These ﬁndings provide new insights into the role of gender in the choice of apology strategies in Algerian Arabic.